2020
DOI: 10.1186/s13000-020-00938-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting cytological results of endoscopic ultrasound guided-fine needle aspiration during learning

Abstract: Background: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is a standard procedure used to obtain tissue samples for diagnosis of solid retroperitoneal tumours. However, this procedure demands high technical expertise and requires a strong learning curve. Our aim was to identify factors associated with falsenegative EUS-FNA results during the learning for endoscopists.Methods: Our retrospective analysis was based on the EUS-FNA specimens collected by two novice endoscopists in 200 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Furthermore, there were no factors affecting the FNB cytopathological diagnosis rate in this study, which was also comparable with those of our previous study [21] that endoscopists who had achieved the learning curve of conventional EUS-FNA could overcome the difficulty of EUS tissue sampling, such as those due to chronic pancreatitis. Regarding the learning curve, a previous study showed that more than 40 procedures could achieve a stable success rate of conventional EUS-FNA [21]. In this study, there was no obvious difference in the success rate of cytopathological diagnosis along the time sequence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, there were no factors affecting the FNB cytopathological diagnosis rate in this study, which was also comparable with those of our previous study [21] that endoscopists who had achieved the learning curve of conventional EUS-FNA could overcome the difficulty of EUS tissue sampling, such as those due to chronic pancreatitis. Regarding the learning curve, a previous study showed that more than 40 procedures could achieve a stable success rate of conventional EUS-FNA [21]. In this study, there was no obvious difference in the success rate of cytopathological diagnosis along the time sequence.…”
Section: Discussionsupporting
confidence: 89%
“…The number of conventional FNB needle passes in our study was also compatible with those of another randomized controlled trial that suggested three to four passes [20]. Furthermore, there were no factors affecting the FNB cytopathological diagnosis rate in this study, which was also comparable with those of our previous study [21] that endoscopists who had achieved the learning curve of conventional EUS-FNA could overcome the difficulty of EUS tissue sampling, such as those due to chronic pancreatitis. Regarding the learning curve, a previous study showed that more than 40 procedures could achieve a stable success rate of conventional EUS-FNA [21].…”
Section: Discussionsupporting
confidence: 89%
“…2), with a 50% fall in 2019 in comparison to 2017 numbers. The shift to imageguided aspirates for superficial lesions is highlighted by many authors in the USA and Europe [2][3][4]8]. In our study, IGFNA for thyroid and breast (both superficial sites) accounted for 80% of procedures in the year of 2019 (shown in Fig.…”
Section: Discussionmentioning
confidence: 62%
“…The endoscopic and endobronchial ultrasound (EUS/EBUS)-guided procedures for the lung, mediastinum, and pancreatic lesions are becoming more popular since they are minimally invasive with lower complication rates vis-a-vis image-guided FNA (IGFNA) [2]. The experienced endoscopist coupled with adequate workload is required for adoption of EUS/EBUS procedures, thereby limiting this practice to large tertiary care centres [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly defined quality indicators apply for colonoscopies and ERCP: the cecum intubation rate [ 14 ] for colonoscopy and cannulation of the native papilla of Vater for ERCP [ 15 ]. Unfortunately, there is no clear quality indicator for EUS, but the competence of examiners obviously increases with the number of examinations carried out [ 16 , 17 ]. On that account, it is difficult to define a universal procedural criterion for EUS that would apply to all EUS procedures.…”
Section: Training and Learning Curvementioning
confidence: 99%